The American research university from World War II to world wide web : governments, the private sector, and the emerging meta-university - Vest, Charles M. (Clark Kerr lectures on the role of higher education in society ;, 2007)
Forty years after Clark Kerr coined the term 'multiversity', the American research university has continued to evolve into a complex force for social and economic good. This volume explores the contemporary state of the research university system, offering a multifaceted view of the university at the beginning of a the century.